AN ANALYSIS OF DEDUCTIVE AND INDUCTIVE APPROACHES IN TEACHING GRAMMAR AT SMPN 2 KOTA TANGERANG - Abdul Rohim; Dania Farahdila; Yudhie Indra Gunawan (Globish: An English-Indonesian Journal for English, Education, and Culture, 2021)
The objective of this research is to know and analyze the deductive and inductive approaches in teaching grammar used by english teachers at SMPN 2 Kota Tangerang. The researchers used descriptive qualitative method. The data of this research were collected through the observation of teaching and learning activities in the classroom of four english teachers at SMPN 2 Kota Tangerang. The result of the research showed that the four english teachers used either deductive approach or inductive approach, it can be seen from the way they were teaching, they chose and used either deductive approach or inductive seen by the steps that implemented by the teacher in teaching grammar, the role  of teacher and students in the teaching and learning activities. The three of four English teachers at SMPN 2 Kota Tangerang used or applied deductive approach in the classroom and one of them still used and applied inductive one. As for the used of an approach, the researchers got a result of the dominance approach used by the English teachers at SMPN 2 Kota Tangerang was deductive.